STRATEGIC PLAN IMPLEMENTATION AND INTERNAL EFFICIENCY IN NIGERIAN UNIVERSITIES - A. Y. Abdulkareem; O. P. Akinnubi; S. Oyeniran (European Scientific Journal, ESJ, 2012)
In recent time, concerted efforts have been made on strategic planning to achieve internal efficiency in the school system. In fact, strategic planning, as a systematic and comprehensive analytical process that scans the internal and external environment of an institution, is more than ever before now receiving attention as a viable alternative in institutional management. This paper intently examined the relationship between strategic plan implementation and internal efficiency in Nigerian universities. The descriptive survey research method was used. Two thousand seven hundred lecturers were used as participants in the study. “Strategic Plan Implementation Questionnaire” (SPIQ) and “Internal Efficiency Checklist” (IEC) designed by the researchers and validated by six expe,rts in the field of Educational Management in the University of Ilorin were used to gather necessary data. Refined Cohort Wastage Rate and Graduation Rate were used to answer three research questions raised in the study. Pearson product-moment correlation statistical analysis was used to test the research hypothesis formulated at .05 level of significance. The findings of the study revealed that: only 11.5% of the respondents indicated that the level of implementation of strategic plan in their universities was low; wastage rate in the universities was low with a mean of 19%; graduation rate was high in each of the universities with a mean of 88%; there was significant relationship between strategic plan implementation and internal efficiency in the universities (calculated r-value= .135 > critical r-value =.06, p < .05). Based on the findings, it was recommended, among others, that universities’ management, staff and students should be more committed to the implementation of strategic plan to achieve internal efficiency in their institutions.